THE NATURE OF Mn-Mn COUPLING IN Mn-Ni-Al ALLOYS - REDNIC, V.; COLDEA, M.; POP, V.; NEUMANN, M. (Studia Universitatis Babeș-Bolyai Physica, 2021)
The occurrence of ferro - and antiferromagnetism in Mn-Ni-Al alloys is governed by the sign of the direct exchange interaction between the Mn magnetic ions. Experimentally has been found that, if the separation between the Mn magnetic ions is greater than the critical value dcr= 2.91 Å, they are ferromagnetic and if the distance is less than the critical value, they are antiferromagnetic. The value of Mn local magnetic moment depends on the number of Al atoms in the first vicinity but the dominant factor is the Mn-Al distance. The nature of Mn-Mn exchange coupling was studied through X-ray diffraction, magnetic and XPS measurements.